KOMODIFIKASI MAKANAN DAN SIGNIFIKASI IDENTITAS: STUDI SOSIOLOGIS BUDAYA KONSUMSI SIMBOLIK MAHASISWA DI KOTA BANDUNG - Ahmed Dipa Suparwanto; Risti Regina Putri; Daniel Andika Nugroho; Radik Mahardika; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
The phenomenon of food consumption among young people today is not only aimed at fulfilling basic needs but has also become part of lifestyle and a symbol of social status. In the context of modern consumer culture, consumption activities are often interpreted as an effort to express identity and social position within a particular environment. This is in line with the concept of symbolic consumption, which emphasizes that consumption is no longer merely function-oriented but also carries social meaning ).This study aims to understand how food consumption is interpreted as a representation of status among university students in Bandung. The findings show that the choice of dining places is not solely based on necessity, but is also influenced by trends, peer environment, and the desire to build self-image. Certain cafes or dining places are chosen due to their symbolic value, such as being modern, aesthetic, and up-to-date.The findings also indicate that the consumptive lifestyle among students is closely related to the effort to construct social identity in public spaces, especially through social media and peer interactions. Therefore, food consumption among students can be understood as part of social practices related to identity and status formation in everyday life.